Leisure and Quality of Life – LQOL-70: An Instrument of Evaluation of Quality of Work Life Based on Leisure - Pilatti, Luiz Alberto; Pedroso, Bruno; Herrera Cantorani, José Roberto (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2022)
The paper is the result of studies regarding quality of life, especially concerning the workers’ quality of life. Based on these studies, an instrument to evaluate quality of life was elaborated. Directed mainly to individuals connected to the productive environment, the instrument developed is based on free time categories present in the Norbert Elias theory. The issues that compose the instrument rely on relevant aspects belonging to the physiological, psychological and sociological spheres. Initially, a pilot application to validate the instrument was carried out. All the employees from the “test” company were the questionnaire respondents, to guarantee the universe of the sample. From the results of the application, based on Cronbach’s alpha coefficient, the validation of the developed instrument was obtained. A re-test was also applied to guarantee the consistency of the instrument. Without doubts, the leisure is an inseparable factor in the quality of life. Through this study, it is attempted to make feasible an instrument with psychometric satisfactory characteristics, easy to fill out and not requiring the use of Statistical Package for the Social Sciences (SPSS) syntax.